Traditional Silvipastoral Systems: An Important Sustainable Agroforestry System for Greening, Restoration of Wasteland and Livelihood Security in Himachal Pradesh, India - Lata, Swaran; Kamakshi; Paul, Shiv; Barman, Tanay; Sharma, Drishti (Indian Forester, 2024)
In Himachal Pradesh, the practice of agroforestry by local inhabitants is an age-old practice. Silvo-pastoral systems are one of the most important agroforestry system types which benefit farming communities through contributing to daily livelihood needs viz., fodder, fuel, timber, medicines etc., and in nutrient recycling, soil and water conservation, improving ecosystems through increasing above ground and below ground carbon stock and mitigation of climate change. Considering these, a study on plant species existing in traditional silvipastoral land use system types was conducted in representative villages of all four agro-climatic zones of Himachal Pradesh. Grewia optiva, Bauhinia variegata, Terminalia spp., Phyllanthus emblica, Myrica esculenta, Rhododendron arboreum, Juniperus polycarpos, Salix spp., Prunus armeniaca, Prunus mira, Pinus gerardiana, Bamboo spp., Bauhinia vahlii, Vitex negundo, Punica granatum, Hippophae spp., Berberis spp. and Bergera koenigii are high potential species growing in silvipastoral systems contributing significantly in improving the livelihood of local communities and ecology of the region. Given the significant potential of silvopastoral systems in enhancing green cover, productivity of degraded and wastelands, and livelihoods for farming communities, urgent collaborative efforts are essential to develop improved silvopastoral systems.